The Oxford History of the British Empire - Louis, William Roger, 1936-; Canny, Nicholas, 1944-; Marshall, P. J. (Peter James); Porter, A. N. (Andrew N.); Brown, Judith M. (Judith Margaret), 1944-; Winks, Robin W.; Low, Alaine M. (Oxford [England] ; New York : Oxford University Press, 1998)
The Oxford History of the British Empire is a major new assessment of the Empire in the light of recent scholarship and the progressive opening of historical records. It deals with the interaction of British and non-western societies from the Elizabethan era to the late twentieth century, aiming to provide a balanced treatment of the ruled as well as the rulers, and to take into account the significance of the Empire for the peoples of the British Isles. All five of the volumes in this series fully explore economic and social trends as well as political ones.
v. 1. The origins of empire / Nicholas Canny, editor ; Alaine Low, associate editor -- v. 2. The eighteenth century / P.J. Marshall, editor -- v. 3. The nineteenth century / Andrew Porter, editor ; Alaine Low, associate editor -- v. 4. The twentieth century / Judith M. Brown and Wm. Roger Louis, editors -- v. 5. Historiography / Robin W. Winks, editor.
Includes bibliographical references and indexes.
Keywords: Imperialism -- History; British colonies; Great Britain -- Colonies -- History; Great Britain -- Colonies -- History; History